Inflammation leads through PGE/EP3 signaling to HDAC5/MEF2‐dependent transcription in cardiac myocytes. Issue 7 (15th June 2018) - Tóth, András D; Schell, Richard; Lévay, Magdolna; Vettel, Christiane; Theis, Philipp; Haslinger, Clemens; Alban, Felix; Werhahn, Stefanie; Frischbier, Lina; Krebs‐Haupenthal, Jutta; Thomas, Dominique; Gröne, Hermann‐Josef; et al.
Abstract: The myocyte enhancer factor 2 (MEF2) regulates transcription in cardiac myocytes and adverse remodeling of adult hearts. Activators of G protein‐coupled receptors (GPCRs) have been reported to activate MEF2, but a comprehensive analysis of GPCR activators that regulate MEF2 has to our knowledge not been performed. Here, we tested several GPCR agonists regarding their ability to activate a MEF2 reporter in neonatal rat ventricular myocytes. The inflammatory mediator prostaglandin E2 (PGE2 ) strongly activated MEF2. Using pharmacological and protein‐based inhibitors, we demonstrated that PGE2 regulates MEF2 via the EP3 receptor, the βγ subunit of Gi/o protein and two concomitantly activated downstream pathways. The first consists of Tiam1, Rac1, and its effector p21‐activated kinase 2, the second of protein kinase D. Both pathways converge on and inactivate histone deacetylase 5 (HDAC5) and thereby de‐repress MEF2. In vivo, endotoxemia in MEF2‐reporter mice induced upregulation of PGE2 and MEF2 activation. Our findings provide an unexpected new link between inflammation and cardiac remodeling by de‐repression of MEF2 through HDAC5 inactivation, which has potential implications for new strategies to treat inflammatory cardiomyopathies. Synopsis: Understanding the link between cardiac inflammation and heart failure is key to develop therapeutic strategies for inflammatory cardiomyopathies. Here, an inflammatory pathway induced by prostaglandin E2 (PGE2 ) is reported to activate MEF2, well known in the setting of adverse cardiac remodeling. Prostaglandin E2 induces MEF2 via multiple signaling pathways, consisting of EP3 receptor, Gi/o ‐βγ, Tiam1, Rac1, PAK2 and PKD, converging on HDAC5 by regulating its nucleo‐cytoplasmic shuttling. Cardiac inflammation elevates the levels of PGE2 and activates MEF2 in vivo . The presented findings strongly imply a novel yet unrecognized link between cardiac inflammation and adverse remodeling. Abstract : Understanding the link between cardiac inflammation and heart failure is key to develop therapeutic strategies for inflammatory cardiomyopathies. Here, an inflammatory pathway induced by prostaglandin E2 (PGE2 ) is reported to activate MEF2, well known in the setting of adverse cardiac remodeling.